Digital media and K–12 mathematical literacy: A systematic review of comparative studies - Navel Oktaviandy Mangelep; Frisca Mareyta Pongoh; Silvana Enjelina Bander; Imriani Moroki; Christari Lois Palit; Gabriella Hillary Wenur; Kinzie Feliciano Pinontoan (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
The development of educational technology has created significant opportunities to improve students' mathematical literacy through the integration of digital media into mathematics instruction. This study systematically reviews and synthesizes comparative evidence on digital media versus traditional teaching methods in K–12 mathematical literacy. As a qualitative systematic review rather than a meta-analysis, it characterizes reported findings rather than establishing pooled causal effectiveness. Forty quantitative studies were selected based on predefined inclusion and exclusion criteria, with screening documented in a PRISMA flow diagram covering experimental designs, digital media interventions, and quantitative literacy measures. Methodological quality was appraised using a structured risk-of-bias assessment. Most studies reported gains in problem-solving, comprehension, spatial reasoning, and higher-order thinking. Interactive software, augmented reality, and educational games boosted motivation through visualization, personalization, and feedback, despite persistent limitations in devices and access. These findings are broadly consistent with digital learning functioning as an adaptive pedagogical strategy. However, the strength of evidence varied with study quality, and most studies did not report comparable effect sizes, limiting cross-study conclusions. This study enriches the knowledge base on technology-based mathematics education and provides an empirical foundation for teachers, policymakers, and researchers to design more contextual, interactive, and literacy-oriented mathematics learning for the 21st century.